Contemporary Europe and South Asia - International Conference on Europe and South Asia: 500 Years (1998 Calicut, India); Vivekanandan, B.; Giri, D. K. (New Delhi Concept Pub. Co., 2001)
Papers presented at International Conference on Europe and South Asia: 500 Years, held in May 1998 at Calicut.
Keywords: South Asia -- Relations -- Europe -- Congresses; Europe -- Relations -- South Asia -- Congresses